Analysis of caesarean sections with the Robson’s ten group classification system - Laya, Meka Kamala; Sree, M. Vijaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Caesarean section rates are increasing globally. For feedback and audit of the caesarean section rate and its optimization in clinical setups worldwide, there was a lack of a classification tool that can be used internationally for which WHO recommended the Robson classification as a tool for monitoring and auditing caesarean delivery rates in 2016. Methods: All women who underwent caesarean section in our institute were included in our study. Exclusion criteria include all mothers who underwent vaginal delivery in our institute and those women with missing records. The study population included 82 women who underwent caesarean in our hospital during the January 2022 to December 2022 period. Results: History of previous section was seen in 45 (54.88%) women. Distribution of all deliveries performed during the study period in accordance to Robsons criteria showed majority of women (29.7%) belonged to category 5a and category 10, followed 21 (25.61%) women in category 1. Data did not categorize any women in category 3 and 7. The most common indication for caesarean seen in our study was previous LSCS seen in 39 (47.56%) women. Conclusions: According to Robsons criteria group 5 and group 10 were the groups found to be majorly contributing the most to the caesarean section in our study. There is a need to evaluate existing management protocols and further studies need to be conducted into the indications of CS and outcomes in our setting are needed to design tailored strategies and improve outcomes.